Malmquist Productivity Index Approach in Assessing Performance of Commercial Banks: Evidence from Nepal - Pathak, Hari Prasad (NRB Economic Review, 2019)
Using the DEA-based Malmquist total factor productivity index, this article measures the total factor productivity of Nepalese commercial banks during the period 2010-2011 to 2016-2017. It also examines whether the ownership structure and size of banks affect their efficiency. An input-oriented DEA model is used with aggregate panel data covering all the 28 commercial banks that are currently operating in Nepal. This article adopts constant returns to scale approach to measure and compare the efficiency and productivity of banks and to establish a benchmark for their performance. Interest expense, operating non-interest expense, deposits and labor are used as inputs variables and interest income, operating non-interest income and loan and advances as outputs variables. These data are extracted from the annual reports of the respective commercial banks. The mean efficiency score measured in terms of total factor productivity change resulted 1.008, which indicates that the efficiency level of Nepalese commercial banks has been increasing very slowly at the rate of 0.8% annually. Ownership structure of the banks influences marginally on the efficiency level of banks. The domestic private banks are relatively more efficient than the joint venture banks and the latter are comparatively more efficient than the public banks. The size of banks makes no significant difference in the efficiency level of banks.